OPTIMASI PEMILAHAN SAMPAH MELALUI PENGEMBANGAN BAK PEMILAH SAMPAH DALAM UPAYA PENCEGAHAN STUNTING - Dhanny Diharja, Adnan; Khalisa, Hilda; Dhava Sanggara, Renalda; Yuliana Rahmat, Delli (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2023)
Background: Waste management by burning can lead to respiratory tract infections, which if it occurs repeatedly in toddlers can increase the risk of stunting. Objective: In dealing with this problem, the creation of waste sorting tanks can be carried out to develop the community's ability to manage household waste so that the habit of burning waste is reduced as an effort to prevent respiratory tract infections and stunting in toddlers, especially in Margamukti Village. Method: Implementation of the activities of making waste sorting tanks is carried out in three stages, namely holding preparation, manufacturing stage, and evaluation stage. Result: The results of the activity of making waste sorting tanks show changes in habits and the ability of the community in waste management. Conclusion: With enthusiasm and support from various parties, student efforts to solve waste management problems in Margamukti Village by making waste sorting tanks as the provision of temporary waste disposal facilities has been successfully carried out.